Iptycene-functionalized silica gel for the purification of fullerenes using flash chromatography. Issue 31 (30th March 2017) - Selmani, Serxho; Yue Shen, M.; Schipper, Derek J.
Abstract : A stationary phase containing bent aromatic molecules interacts strongly with fullerenes, allowing for their purification on a relatively large scale. Abstract : Fullerenes have attracted much attention since their discovery but research efforts are plagued by the challenge of fullerene purification. We have developed a functionalized silica gel that allows for the purification of fullerenes using standard flash chromatography. The method relies on a stationary phase consisting of bent aromatic molecules that interact strongly with different types of fullerenes, allowing for their purification on a relatively large scale.